Power system protective relaying - Das, J. C. (Power systems handbook ;, 2018)
This book focuses on protective relaying, which is an indispensable part of electrical power systems. The text covers smart grids, integration of wind and solar generation, microgrids, and MMPRs as the driving aspects of innovations in protective relaying. Topics such as cybersecurity and instrument transformers are also explored. Many case studies and practical examples are included to emphasize real-world applications.